DOP coefficients in GNSS observations - Kamil Maciuk (Budownictwo i Architektura, 2015)
Integrated GNSS (GPS+GLONASS) satellite measurements carry a number of benefits. The main advantages are especially possibilities of conducting measurements in areas where use of a single satellite system was not impossible so far. In this paper number of visible satellites and DOP coefficients values in terms artificial horizon obstacles were analysed. Paper also discusses benefits of including additional observations from other navigation satellite systems.